2011
DOI: 10.1097/cmr.0b013e32834577c8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in survival of cutaneous melanoma are age dependent

Abstract: This study identified sex differences in clinical presentation and survival for primary cutaneous melanoma without clinical evidence of metastasis at diagnosis from 1976 to 2008 in southern Germany. Melanoma-specific survival curves and estimated survival probabilities were generated using the Kaplan-Meier method. Multivariate survival analyses were carried out using the Cox modeling. Male patients had significantly thicker and more frequently ulcerated tumors and a lower 10-year disease-specific survival (DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Ulceration and increased thickness have already been identified as the most powerful tumor-related poor prognostic predictors (10,12). Similarly, the present study also observed that men had thicker and ulcerated lesions and that they had tumors located more often on the trunk, compared with women, in whom the tumors were more often located in the extremities.…”
Section: Univariate Analyses Multivariate Analyses ------------------supporting
confidence: 71%
See 1 more Smart Citation
“…Ulceration and increased thickness have already been identified as the most powerful tumor-related poor prognostic predictors (10,12). Similarly, the present study also observed that men had thicker and ulcerated lesions and that they had tumors located more often on the trunk, compared with women, in whom the tumors were more often located in the extremities.…”
Section: Univariate Analyses Multivariate Analyses ------------------supporting
confidence: 71%
“…The first hypothesis was controverted and the second hypothesis was advocated by the fact that the female survival advantage persisted even following adjustment for factors such as Breslow's thickness, and that lymph node and visceral organ metastases did not affect the higher survival rate of female patients (4,(5)(6)(7)(8)(9)(10)(11). Thus, it was concluded that the aggressiveness of the disease did not affect the survival benefit of female melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies, the female advantage disappeared at postmenopausal ages. 5,6,19,20 However, the majority of studies found that the female survival advantage persisted in these older groups, even among stage III and IV melanoma. [1][2][3][4][21][22][23][24][25][26] Therefore, combining our results and these previous studies, we conclude that females have a survival advantage in both premenopausal and postmenopausal age.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3] The main arguments for rejecting these explanations were the persistence of the female advantage after adjustment for prognostic indicators presumably related to behavioral aspects (e.g., Breslow thickness and primary tumor location) and the persistence of the female advantage when melanoma metastasized to lymph nodes and distant organs. [1][2][3][4][5][6] Therefore, it is more likely that the female survival advantage is caused by some biological difference, which might be either tumor-related (e.g., males have more aggressive melanomas) or host-related (i.e., females are better able to resist progression and metastasis).…”
mentioning
confidence: 98%
“…While still incompletely elucidated, understanding of the precise cellular and molecular mechanisms by which hormones alter these various immune functions is likely to play a crucial role in understanding gender differences in response not only to autoimmune diseases, but also chronic inflammatory conditions, human immunodeficiency virus (HIV) infection, cancer, bone marrow transplantation, or graft-versus-host disease (GVHD). For instance, gender has been shown to be an important and independent predictor of clinical outcome and survival in cutaneous melanoma, with premenopausal females (but not women older than 60 years) experiencing an improved prognosis [72,73]. The presence of sex steroid receptors in hematopoietic elements [24,58,66], as well as thymic and BM stromal cells [74][75][76] suggests that they may have a direct or indirect effect on immunity and hematopoiesis.…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 99%